RNA-Seq Analysis of Developing Grains of Wheat to Intrigue Into the Complex Molecular Mechanism of the Heat Stress Response - Paul, Surinder; Duhan, Joginder Singh; Jaiswal, Sarika; Angadi, Ulavappa B.; Sharma, Ruchika; Raghav, Nishu; Gupta, Om Prakash; Sheoran, Sonia; Sharma, Pradeep; Singh, Rajender; Rai, Anil; Singh, Gyanendra Pratap; et al. (Frontiers in Plant Science, 2022)
Heat stress is one of the significant constraints affecting wheat production worldwide. To ensure food security for ever-increasing world population, improving wheat for heat stress tolerance is needed in the presently drifting climatic conditions. At the molecular level, heat stress tolerance in wheat is governed by a complex interplay of various heat stress-associated genes. We used a comparative transcriptome sequencing approach to study the effect of heat stress (50 C above ambient threshold temperature of 20 °C) during grain filling stages in wheat genotype K7903 (Halna). At 7 DPA (days post-anthesis), heat stress treatment was given at four stages: 0, 24, 48 and 120 hours. In total, 115,656 wheat genes were identified, including 309 differentially expressed genes (DEGs) involved in many critical processes such as signal transduction, starch synthetic pathway, antioxidant pathway and heat stress-responsive conserved and uncharacterized putative genes that play an essential role in maintaining the grain filling rate at the high temperature. A total of 98412 Simple Sequences Repeats (SSR) were identified from de novo transcriptome assembly of wheat and validated. The miRNA target prediction from differential expressed genes was performed by psRNATarget server against 119 mature miRNA. Further, 107107 variants including 80936 Single nucleotide polymorphism (SNPs) and 26171 insertion/deletion (Indels) were also identified against de novo transcriptome assembly of wheat and wheat genome Ensembl version 31. The present study enriches our understanding of known heat response mechanisms during the grain filling stage supported by discovery of novel transcripts, microsatellite markers, putative miRNA targets and genetic variant. This enhances gene functions and regulators, paving the way for improved heat tolerance in wheat varieties, making them more suitable for production in the current climate change scenario.